2017
DOI: 10.1063/1.5007850
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms for solid-state processing and grain growth with microstructure alignment in alnico-8 based permanent magnets

Abstract: An estimated 750,000 new hybrid electric and plug-in battery vehicles, most with permanent magnet synchronous alternating current (PMAC) drive motors, took to the road in 2016 alone. Accompanied by 40% year over year growth in the EV market significant challenges exist in producing large quantities of permanent magnets (on the order of tens of millions) for reliable, low-cost traction motors [IE Agency, Energy Technology Perspectives (2017)]. Since the rare earth permanent magnet (REPM) market is essentially 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In addition, a high degree of autonomous control can shorten the cycle of results conversion in the new energy sector and reduce the initial cost of discovery [24]. Studies have shown that the electric vehicle market grew by 40% year-on-year in 2018, and manufacturing is possible with core components such as traction motors that are independently developed and safe [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, a high degree of autonomous control can shorten the cycle of results conversion in the new energy sector and reduce the initial cost of discovery [24]. Studies have shown that the electric vehicle market grew by 40% year-on-year in 2018, and manufacturing is possible with core components such as traction motors that are independently developed and safe [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Significant effort has been devoted to developing simple non-cast approaches for achieving [001] easy axis aligned alnico magnets. [46][47][48][49][50][51] Abnormal grain growth (AGG) is detected during the compaction of the pre-alloyed gas atomized spherical powders. This leads to increased texturing control without the costly directional casting, i.e., energy product increases from 38 kJ/m 3 to 52 kJ/m 3 (4.8-6.5 MGOe) primarily because of $ 24% increase of loop squareness during the AGG process.…”
Section: Alnicomentioning
confidence: 99%
“… 11 Kassen et al proposed that the electric vehicle market would grow by 40% year-on-year in 2018. 12 Only with independent research and development, safe and reliable manufacturing to produce traction motors and other core components can have the core competitiveness of IM. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Tabor believed that a high level of IM could shorten the transformation cycle of new energy vehicles and reduce initial cost . Kassen et al proposed that the electric vehicle market would grow by 40% year-on-year in 2018 . Only with independent research and development, safe and reliable manufacturing to produce traction motors and other core components can have the core competitiveness of IM …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation